A Study On Service Quality Dimensions Of Domestic Airline Industry In India - Dr K K Ramachandran (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Air transportation acts as a catalyst for economic development and trade by facilitating goods and passenger movement domestically and around the world. The robust growth in Indian Airline Industry has redefined the way people travel in India. In the recent past, the cost of air transportation has fallen and this has encouraged many middle income travelers to travel by air. Open sky policy is being followed in the airline industry and growing stiff competition has changed the rules of the game. The pressure to provide better customer services has never been greater. Yet the challenge to reduce operating costs is equally strong. Automation of services is playing a key role in attaining these goals and many innovative solutions are being deployed. Plethora of software solutions are designed and implemented to improve the passenger’s journey, streamline and integrate airline and airport operations, such as internet-based reservation systems, electronic ticketing, automated check-in, baggage handling, meals, enterprise-wide customer relationship solutions and frequent flyer programmes. The objective of all such solutions is to deliver the highest quality of customized services to the passengers at affordable costs. In the airline business, service quality indicates that, all passengers are entitled to receive any or all relevant information about their trip, such as any changes in scheduled flight timings or route diversions, giving fare information, including extras such as departure taxes, reserve seat charges and ad-hoc surcharges. Airlines should be committed to providing quality onboard services to passengers. Focusing on service quality is the need of the hour if the airline company aspires to improve market share and to enhance its financial performance. This paper identifies different service quality dimensions and assesses its relevance with reference to passenger’s satisfaction. It also measures the gap between expectations and perceptions of the passengers so that strategies can be implemented to improve the quality of service and increase airlines profitability and market share.